Closing the gaps? An organizational behavior analysis of U.S.-Mexico security cooperation - Roland, Naomi Verbong (2015)
The scope of this dissertation is limited to the years 2007 to 2013, incorporating the formation and attempted reform of the initiative in 'beyond Merida.' Expanding on the seminal work of Essence of Decision by Graham Allison and Philip Zelikow, this dissertation will explain US government behavior towards Mexico." In the next chapter, I outline the Merida Initiative, placing it in the context of US-Mexico bilateral relations. In chapter three, I describe Allison and Zelikow's three models of foreign policy analysis: rational actor, governmental politics, and organizational behavior. I outline and expand on the relevance of Allison and Zelikow's model II, creating three hypotheses relevant to this study. In chapter four, I analyze the Merida Initiative, using two guiding questions from the hypotheses of organizational behavior. Through the use of primary source analysis, I show how different agencies used Merida Initiative programs to their organizational advantage. I conclude with the implications of this analysis for the study of US-Mexico security cooperation and foreign security assistance as a whole.